2011
DOI: 10.1002/nau.21116
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self‐reported double incontinence in the Urban population of a Brazilian city

Abstract: The study allowed a better understanding of the epidemiology of double incontinence and may contribute to the development of public policies and programs for primary and secondary prevention and treatment of double incontinence, at least at the municipal level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
0
17
0
3
Order By: Relevance
“…Besides facilitating international comparison, this choice was justified by the fact that approximately 20% of the individuals denied the condition when questioned, leading to a lower prevalence than what is real. Several studies reported that some elderly are uncomfortable or ashamed when interviewed (24). Also, ICIQ-SF was applied to verify the degree of influence of incontinence on the life of the elderly.…”
Section: Resultsmentioning
confidence: 99%
“…Besides facilitating international comparison, this choice was justified by the fact that approximately 20% of the individuals denied the condition when questioned, leading to a lower prevalence than what is real. Several studies reported that some elderly are uncomfortable or ashamed when interviewed (24). Also, ICIQ-SF was applied to verify the degree of influence of incontinence on the life of the elderly.…”
Section: Resultsmentioning
confidence: 99%
“…Few data exist about the prevalence of double incontinence in general female population. In a recent published study, the prevalence of self‐reported double incontinence in women aged 18 and older in the urban population of a Brazilian city was 5% 6. In a study in the Netherlands in a general population of women aged 45–85 years, the prevalence rate of UI associated to anal incontinence, with and without flatal incontinence, was estimated by 35.4% and 10.3%, respectively 7.…”
Section: Introductionmentioning
confidence: 98%
“…This condition is related to other health problems such as dementia, urinary tract infection, being bedridden, cognitive or physical impairment, among others . Furthermore, incontinence causes hygienic and skin problems, as well as a negative impact on quality of life, which may result in reduced self‐esteem, depression, and social isolation . Admission to a nursing home (NH) can influence continence among new residents and UI in this setting tends to be more severe and costly.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the impact of UI, this is an under‐diagnosed and under‐treated health problem, due to patient embarrassment and the misconception that incontinence is a natural part of the aging process, and also due to the lack of motivation of health professionals to investigate this condition . In Brazil, the range of UI rates in the institutionalized elderly in the scientific literature is broad, varying between 22% and 100%, due to different survey methods and sample characteristics.…”
Section: Introductionmentioning
confidence: 99%